Spatial Analysis of Macro Economic in Central Java (PDRB Analysis in Year 1993-2003) - Eddy Kiswanto (Forum Geografi, 2005)
This paper aims to study the spatial analysis macroeconomics condition in central Java from 1993-2001 base on PDRB analysis. Central Java stands in the last position in the economic in Central Java based on PDRB variable and economic growth is in the lowest category in the comparation with another provinces in Java. This is reason why Central Java is categorized as "LL" (Low low). One of the prime sectors in Central Java is small medium scale enterprises which is dominated 30% of national market, but since the economic crisis stroke in 1997 the manufacture sector, especially industry and processing had collapse. In 1996-1997, the level of manufacture growth increased to 14.4% but then decreased until minus 19.3%. This condition caused by bankruptcy to many of the industries. The poverty profile in Central Java from 1999-2003 is average 23.3% from the total population every years. Central Java stepping to number 2 in level of poverty absolute number 1. In poverty relativity level, Central Java became number 1 in Java from 2002-2003 with the level of poverty reached above the national average. This fact shows the unsuccessfully effort in reducing the poverty level.